BLOOD DONATION AS A HEALTH INTERVENTION: BENEFITS, RISKS AND PHYSIOLOGICAL ADAPTATIONS - Piotr Bartnik; Mikołaj Wiśniewski; Weronika Buczek; Jolanta Wiśniewska; Magdalena Pietrzak; Karolina Barzyk; Urszula Marzec (International Journal of Innovative Technologies in Social Science, 2025)
Background: Blood donation, traditionally regarded as a „priceless gift of life” and altruistic act of supporting healthcare systems, has increasingly been examined as a potential health - modifying intervention for donors themselves. This review synthesizes current evidence on the physiological benefits, potential risks and adaptive responses associated with regular blood donation. Health benefits of blood donation include reductions in body iron stores, which can transform into decreased oxidative stress, improved metabolic profiles and lower long - term cardiovascular risk in selected populations. Clinical trials suggests potential modulations in inflammatory markers and improved vascular function following regular donation. However, blood donation is not procedure without risk. There are some acute side effects such as for example vasovagal reactions, temporary weakness and reduced exercise tolerance, while long - term concerns include iron - deficiency anemia, impaired physical performance in high - demand athletes and possible cumulative effects of frequent phlebotomy. Physiological adaptations to recurrent blood loss are for example enhanced erythropoiesis, plasma volume expansion, and changes in iron - regulatory pathways which play a central role in shaping donors’ responses and may differ according to sex, age, nutritional status and donation frequency. By integrating data from clinical trials, epidemiological studies and research this review highlights the complex interplay between the therapeutic potential and physiological cost of blood donation. Understanding these dynamics is crucial for optimizing donor safety, refining eligibility and recovery guidelines and exploring whether periodic blood removal could serve as a targeted intervention in specific clinical or metabolic contexts.Aim: The aim of this study is to investigate the physiological, metabolic and cardiovascular effects of regular blood donation, in particular donor safety, risk factors and potential health benefits associated with regular blood donation.Methods: A review of scientific articles published on ResearchGate and PubMed from 1998 to 2025.Results: Regular blood donation leads to many physiological adaptations, including reduced iron stores, improved lipid profiles, decreased oxidative stress  and lower inflammation. Cardiovascular benefits such as for example reduced risk of myocardial infarction have been reported too. Common side effects include vasovagal reactions, temporary hypotension, and, rarely, iron - deficiency anemia in frequent donors. Overall, blood donation can provide health benefits when monitored appropriately.Conclusion: Blood donation is not only a altruistic act but also a physiological and metabolic intervention. Regular donations are associated with improved cardiovascular and metabolic benefits, reduced oxidative stress and enhanced iron regulation, while side effects remain generally smooth and manageable. With adequate donor screening and monitoring, blood donation can provide significant health benefits, supporting both individual well - being and societal needs for blood supply.